Negative pressure interface material constructed by bioelastomer material as well as preparation method and application of negative pressure interface material

By using biological elastomers, such as PGS and other biomedical materials, prepare a multi -stage negative pressure interface material, solve the problem of being difficult to quickly promote the growth of granulous tissue in large -scale wound treatment, and realize the degradation and degradation of materials and the degradation of materials and the degradation of materials The wound regeneration synchronizes the wound healing efficiency.

CN119367579APending Publication Date: 2025-01-28SHANGHAI NINTH PEOPLES HOSPITAL SHANGHAI JIAO TONG UNIV SCHOOL OF MEDICINE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310897438.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the treatment of large-area wounds, existing negative pressure interface materials are difficult to quickly promote the growth of granulation tissue, and when changing dressings, it is easy to destroy new granulation tissue, resulting in bleeding and pain on the wound.

Method used

Use biological elastic body materials, especially polycogyl glyceride (PGS), combined with other biomedical materials such as PCL or PLGA, and prepare a multi -level negative pressure interface material through 3D printing technology. It has good biodegradable and soft tissue Mechanical bionic performance.

Benefits of technology

This material can promote the rapid growth and wound filling of granulation tissue under negative pressure, and match the degradation rate with the wound regeneration rate, avoiding the problem of material residues and secondary surgical debridement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004350674110000011
    Figure HDA0004350674110000011
  • Figure HDA0004350674110000012
    Figure HDA0004350674110000012
  • Figure HDA0004350674110000013
    Figure HDA0004350674110000013
Patent Text Reader

Abstract

The invention discloses a negative pressure interface material. The negative pressure interface material comprises a bioelastomer material and a biological material. The invention further discloses a preparation method of the negative-pressure interface material, rapid, continuous and large-size 3D printing of the bioelastomer material and the bioelastomer material composite material is realized by using a novel thermosetting material composite 3D printing technology and utilizing solvent compounding and solvent plastification. By utilizing the negative pressure interface material disclosed by the invention, new granulation tissues can rapidly grow by virtue of a biological scaffold under the action of negative pressure, regeneration of a new matrix is efficiently induced, wound surface defects are more rapidly filled, and optimized conditions are provided for later wound surface coverage; meanwhile, in the tissue remodeling stage, the material stent is gradually replaced by the autologous tissue through gradual degradation of the material, and finally the remodeling process is completed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedicine and relates to a negative pressure interface material constructed of a bioelastic material and a preparation method and application thereof. Background Art

[0002] Negative pressure wound therapy (NPWT) is the most rapidly developed and widely used wound treatment technology in the past 20 years. It can be widely used in the treatment of various acute and chronic wounds. The core mechanism of this technology is to create a certain value of negative pressure (generally -55 to 175 mmHg) through a negative pressure dressing with a well-connected porous structure to actively drain wound exudate; at the same time, negative pressure is transmitted to the wound through the negative pressure interface material to efficiently induce angiogenesis and extracellular matrix regeneration, thereby efficiently completing the wound bed preparation and accelerating the wound healing process. The device mainly consists of: negative pressure power source, negative pressure pipeline system, sealing film, negative pressure dressing, and liquid storage tank. Among them, the negative pressure interface material is the part that directly contacts the human wound and needs to meet multiple requirements such as flexibility and reasonable gaps. It is a key subsystem for the effective implementation of negative pressure therapy. Compared with traditional wound treatment technologies, NPWT has more advantages in the treatment of difficult-to-heal wounds such as pressure sores, diabetic foot, and gangrene, reflecting relatively wide applicability and higher treatment efficiency.

[0003] At present, the negative pressure materials commonly used in NPWT treatment at home and abroad are non-biodegradable negative pressure interface materials such as polyvinyl alcohol (PVA) and polyurethane foam (PU). Although this type of material can improve the wound base with high efficiency, this technology is still not satisfactory for filling tissue defects with new matrix. In cases where the wound base is large and there is a lot of necrotic tissue in the base, it is inevitable that a longer period of negative pressure drainage treatment is required; and this type of wound usually requires rapid granulation growth to close the wound. Under the action of continuous negative pressure, the new granulation tissue is easy to grow into the pores of polyurethane foam (see Figure 1 ), which results in the destruction of new granulation tissue when changing the dressing, and causes bleeding and severe pain on the wound surface. Therefore, when existing negative pressure interface materials are used in large-area wound defects, there is often a waste of granulation tissue that needs to grow quickly but has to be removed in part.

[0004] The defects of existing negative pressure interface materials can be improved by seeking to replace existing non-degradable materials, which can achieve both high drainage and facilitate the rapid filling of wound defects with new matrix. The existing clinically used degradable biomaterials for soft tissue repair mainly include: ① Natural degradable materials, such as collagen, chitosan, etc. The characteristics of this type of material are that the degradation products are easily absorbed by the body, but they are mostly gel-like in the body, with poor mechanical properties and too fast degradation. When used as negative pressure interface materials, they are prone to pore blockage and shape collapse. ② Synthetic degradable polymer materials, such as PCL, PLGA, PLLA and other thermoplastic polymer materials. However, the nature of the material itself determines that it does not have elastic properties, resulting in poor structural recovery after being strained by external force; in addition, the degradation time of these materials is too long, which makes their degradation rate and soft tissue regeneration rate mismatched, resulting in long-term residue of negative pressure interface materials and other problems.

[0005] We believe that this new type of negative pressure material must have the following characteristics: ① The pore size of the material is conducive to cell growth, and it has a certain porosity, which can smoothly carry out negative pressure drainage; ② It is easy to process into various shapes to match the specific wound structure of different patients; ③ It has the performance of soft tissue mechanics bionics, soft texture and elasticity, so as to ensure that the material and the wound surface remain in contact with each other when the patient is active, and will not cause excessive friction or pressure on the surrounding soft tissue; ④ It has good biocompatibility and reduces the inflammatory response in wound repair; ⑤ It has a suitable biodegradation rate, so that the degradation rate matches the wound regeneration rate, which not only avoids the secondary surgical debridement trouble of the above-mentioned non-degradable dressings, but also completely degrades the filling material as the tissue regenerates, thereby effectively reducing the defect space. After selecting materials in a large number of experiments and literature, we paid attention to bioelastomers.

[0006] Bioelastomers, that is, biodegradable and biocompatible elastomers, are an important biomaterial that has emerged in recent years. Because they simulate the mechanical characteristics of human soft tissue and adapt to the dynamic mechanical environment of the human body, they are a cutting-edge direction in the biomedical field and have broad application prospects. Among the newly developed bioelastomers, poly(glycerol sebacate), PGS is a prominent representative. PGS is one of the earliest bioelastomers introduced into the field of tissue engineering. It has attracted widespread attention and has been applied to soft tissue fields such as cardiovascular. It is also the bioelastomer material with the most promising clinical transformation prospects. PGS is constructed from glycerol and sebacic acid, both of which are approved by the U.S. Food and Drug Administration (FDA) for clinical use and show excellent in vivo tissue compatibility. In 2020, the PGS-based acrylic modified PGSA cardiac surface bioglue was officially approved by the FDA.

[0007] In recent years, 3D printing technology has made great progress in the field of tissue engineering due to its ability to accurately construct microstructures and its advantages in personalized customization. As a typical thermosetting material, PGS has excellent elasticity and fatigue resistance due to its chemical cross-linking structure produced at high temperature. However, this long-term chemical cross-linking also greatly limits its processing methods, making it difficult to match the continuous processing method of 3D printing. In response to this problem, we have innovatively proposed a 3D printing strategy for salt particle composite ink in the early stage, which has achieved 3D printing molding of a very wide range of thermosetting materials. For the first time, we successfully used extrusion 3D printing technology to prepare PGS elastic scaffolds and obtained an authorized patent: a method for preparing a thermosetting elastomer tissue engineering scaffold with a multi-level pore structure, patent number: ZL201710348151X. However, in its further research, it was found that there are still important problems. Due to the high viscosity and high salt content of PGS prepolymer, there is a risk of needle clogging in the 3D printing process, as well as poor stability, slow printing rate, low yield, and difficulty in large-scale preparation.

[0008] Commonly used negative pressure materials are polyvinyl alcohol foam and polyurethane foam non-degradable dressings. However, clinically it has been found that the volume of the negative pressure dressing itself limits the growth space of the new matrix, and the growth of new tissue in PU will bring about problems such as secondary debridement.

[0009] Among degradable biomaterials, there is a lack of materials that are suitable for soft tissues and can be used under negative pressure conditions. Common tissue engineering scaffold materials cannot simultaneously meet the following requirements: 1. The degradation rate is about 3-6 months, the gaps will not collapse prematurely, and the degradation will not be too slow to affect healing; 2. The performance of soft tissue mechanics bionics, soft texture and elasticity.

[0010] abbreviation:

[0011] NPWT, negative pressure wound therapy

[0012] PVA,polyvinyl alcohol,polyethylene

[0013] PU,polyurethane

[0014] PGS, poly(glycerol sebacate), polyglycerol sebacate

[0015] PCL,polycaprolactone

[0016] PLGA, poly(lactic-co-glycolic acid), poly(lactic-co-glycolic acid)

[0017] PLA,polylactic acid

[0018] PGA,polyglycolideacid,polyglycolide

[0019] PLCL, Poly(L-lactide-co-caprolactone), Poly(L-lactide-co-caprolactone) Summary of the invention

[0020] The present invention uses bioelastic material as raw material to construct a degradable negative pressure interface material, promotes the growth of granulation tissue, fills the wound surface, and thus achieves a rapid healing effect. The negative pressure interface material of the present invention has the following characteristics: 1. It is composed of bioelastic material; 2. It is degradable in the human body and safe; 3. It has no limit on the growth rate of granulation tissue.

[0021] The invention provides a negative pressure interface material, which comprises a bioelastic material and a biomaterial.

[0022] The composition and content of the negative pressure interface material are: 40-100% bioelastic material and 0-60% biomaterial.

[0023] Preferably, the composition and content of the negative pressure interface material are: 60-95% bioelastic material, 5-40% biomaterial.

[0024] Further preferably, the composition and content of the negative pressure interface material are: 80% bioelastic material and 20% biomaterial.

[0025] Wherein, the bioelastic material is PGS and the like.

[0026] The PGS, Poly (glycerol sebacate), is polyglycerol sebacate.

[0027] Wherein, the biomaterial is selected from PCL, PLGA, PLA, PGA, PLCL, etc.; preferably, it is PCL or PLGA.

[0028] The negative pressure interface material used in the present invention is adapted to the mechanical properties of soft tissue as a whole.

[0029] The negative pressure interface material of the present invention is a multi-level structure: the primary structure is the overall macroscopic appearance of 3D printing, the secondary structure is the 3D printed grid drainage channel, and the tertiary structure is the micropores inside the printed fiber unit.

[0030] The present invention utilizes bioelastic materials in combination with biomaterials to adjust the degradation rate, so that the degradation rate of the negative pressure interface material is appropriate, the pores will not collapse in the early stage to affect the patency of the negative pressure drainage, and will give way to granulation tissue in the later stage to meet the growth needs.

[0031] The present invention also proposes a method for preparing a negative pressure interface material, which uses a new type of thermosetting material composite 3D printing technology, solvent compounding and solvent plasticization to achieve rapid, continuous, large-scale 3D printing of bioelastic materials and bioelastic material composite materials. The technology is used to prepare bioelastic materials and negative pressure interface materials of biomaterials, retaining multi-level microporous structures and biomimetic elasticity, and regulating their mechanical properties and degradability.

[0032] The method for preparing the negative pressure interface material specifically comprises the following steps:

[0033] (1) dissolving the bioelastic material and the biomaterial in an organic solvent to obtain a solution;

[0034] (2) stirring and mixing the solution obtained in step (1) with salt particles to obtain a mixture;

[0035] (3) using the mixture obtained in step (2) as a composite ink for 3D printing to obtain a structure;

[0036] (4) Curing and cross-linking the structure obtained in step (3) to obtain a negative pressure interface material.

[0037] In step (1), the bioelastic material is PGS or the like.

[0038] In step (1), the biomaterial is selected from one or more of PCL, PLGA, PLA, PGA, PLCL, etc.; preferably, PCL or PLGA.

[0039] In step (1), the organic solvent is selected from one or more of acetone, tetrahydrofuran, hexafluoroisopropanol, dichloromethane, etc.; preferably, it is tetrahydrofuran.

[0040] In step (1), the mass ratio of the bioelastic material to the biological material is 40-100%:0-60%; preferably, 80%:20%.

[0041] In step (1), the total mass of the bioelastic material and the biomaterial is dissolved in an organic solvent at a ratio of 1-50% (w / v).

[0042] In step (2), the salt particles are selected from one or more of sodium chloride, potassium chloride, sodium sulfate, etc.; preferably, they are sodium chloride particles.

[0043] In step (2), the particle size range of the salt particles is: 1-100 μm; preferably, 20-40 μm.

[0044] In step (2), the mass ratio of the material to the salt particles in the solution is 1:0.5-1:5; preferably, it is 1:2.

[0045] In step (3), the 3D printing parameters include: printing needle size (0.1-1mm), printing path spacing (0.2-5mm), printing temperature (-20~150℃), extrusion pressure (0.01-1bar), and printing rate (0.1-100mm / s); preferably, printing needle size (0.5mm), printing path spacing (1.8mm), printing temperature (30℃), extrusion pressure (0.5bar), and printing rate (30mm / s).

[0046] In step (4), the curing and cross-linking temperature is 80-180°C, the vacuum degree is -0.01 to -0.1Mpa, and it is maintained for 12-48 hours; preferably, the temperature is 100°C, the vacuum degree is 0.05Mpa, and it is maintained for 24 hours.

[0047] After the structure is cured and cross-linked in step (4) of the present invention, a post-processing step is also included: the cured and cross-linked material is immersed in a mixed solution of ethanol and water (10-75%), the internal salt particles, the residual PGS prepolymer that has not been completely reacted, etc. are dissolved and removed, and the water and solvents such as ethanol are removed by washing, air drying, heating, freeze drying, etc. to obtain a negative pressure interface material.

[0048] In a specific embodiment, the preparation method of the negative pressure interface material is: dissolving the total mass of PGS prepolymer and other biomaterials (including but not limited to PCL, PLGA, PLA, PGA, PLCL, etc.) in an organic solvent (acetone, tetrahydrofuran, hexafluoroisopropanol, dichloromethane, etc.) at a ratio of 1-60%, stirring and mixing the obtained solution with salt particles of a certain size obtained by crushing, filtering and screening (sodium chloride, potassium chloride, sodium sulfate, etc.) to obtain a mixture (wherein, the particle size range of the salt particles is: 1-100 μm; the total mass of PGS and other biomaterials to the mass ratio of the salt particles is: 10-80%), ventilating or heating the mixture to volatilize a part of the solvent, so that the mixture is in a paste-like form, so it has good extrudability and the ability to maintain shape. The resulting mixture is then used as a composite ink for 3D printing, and the required printing model and printing parameters are set, including: printing needle size (0.1-1mm), printing path spacing (0.2-5mm), printing temperature (-20-100℃), extrusion pressure (0.01-1bar), printing rate (0.1-100mm / s), etc. The structure of the composite material formed by 3D printing PGS containing salt particles and other biomaterials is placed in a high temperature and vacuum environment, with a temperature of 80-180℃ and a vacuum degree of -0.01 to -0.1Mpa, and maintained for 12-48 hours, so that the PGS is cured and cross-linked to form a stable structure. During the vacuum and heat curing process, the 3D printed structure is required not to undergo obvious collapse, shrinkage, oxidation, or thermal decomposition. It is further immersed in a mixed solution of ethanol and water (10-75%) to dissolve and remove the internal salt particles, the residual PGS prepolymer that has not been completely reacted, etc., and the water and solvents such as ethanol are removed by air drying, heating, freeze drying, etc., so as to obtain a porous 3D printed negative pressure interface material. It is stored in a vacuum drying oven or nitrogen packaging, and sterilized (cobalt-60 gamma ray irradiation, 25-30kGy) for long-term storage and use.

[0049] The invention also provides a negative pressure interface material prepared by the method.

[0050] The invention also proposes the application of the negative pressure interface material in the treatment of acute and chronic wounds.

[0051] The present invention also proposes the application of the negative pressure interface material in repairing various human soft tissue defects.

[0052] The beneficial effects of the present invention include but are not limited to: the present invention can enable the new granulation tissue to grow rapidly along its multi-level microporous scaffold under the action of negative pressure, relying on the negative pressure interface material, effectively inducing the regeneration of new matrix, filling the wound defect faster, and providing optimized conditions for later wound coverage; at the same time, in the tissue remodeling stage, through the gradual degradation of the material, the autologous tissue gradually replaces the material scaffold, and finally completes the remodeling process. The present invention uses 3D printing technology to construct the primary pore structure of the scaffold material (see Figure 2 , 3 ); The present invention also has a multi-level microporous structure that traditional 3D printed stents do not have. The surface and interior of the 3D printed fiber unit contain uniformly distributed microporous structures. These surface micropores increase the roughness of the stent surface, which is beneficial to cell adhesion, while the internal microporous structure provides space for cells to grow into the stent, which is beneficial to the regeneration and fusion of the stent and tissue. The PGS composite multi-level microporous stent constructed by the present invention has been verified in animal experiments (see Example 3 of the present invention for details), and the following conclusions were obtained: 1. In the primary pores, granulation tissue with a large number of functional blood vessels can be observed. 2. In the secondary micropores of the stent, cell growth can be observed. 3. The in vivo degradation of the stent was observed.

[0053] abbreviation:

[0054] PGS,Poly(glycerol sebacate),Poly(glycerol sebacate)

[0055] PCL,Polycaprolactone

[0056] PLGA,poly(lactic-co-glycolic acid),poly(lactic-co-glycolic acid)

[0057] PLA,polylactic acid BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 .The wound did not heal after chest surgery. After 12 days of negative pressure treatment, a large amount of granulation tissue was tightly combined with the polyurethane (PU) foam dressing, and a large amount of dressing remained after hydrodynamic debridement.

[0059] Figure 2 . Flow chart for the preparation of negative pressure interface materials. According to the needs, PGS is mixed with other polymer materials in a certain proportion, and salt particles of selected sizes are added to prepare salt particle composite ink; then 3D printing technology is used to select appropriate parameters to print a grid structure containing secondary pores; the salt particles in the eluted material form tertiary micropores in each fiber material.

[0060] Figure 3.Schematic diagram of the negative pressure interface material structure.

[0061] Figure 4 .General view of negative pressure interface materials (the second from the left is a multi-level microporous scaffold with different proportions of PGS, and the first from the right is a polyurethane foam, both are cut into circles).

[0062] Figure 5 Scanning electron microscope (SEM) images of negative pressure interface material (pure PGS), top view and cross-section view, 50μm and 500μm, specific parameters are as follows:

[0063] Fiber diameter: 440.2±28.7μm (needle size: 1000μm)

[0064] Length: 6cm

[0065] Secondary hole size: 1mm square three-dimensional grid interconnected channel (printing path spacing: 4mm)

[0066] Tertiary pore size: 10.31±5.85μm (salt particle size range: 5-50μm)

[0067] Fiber stacking: 90° (preparation angle: 45 / 60 / 90°)

[0068] Layer height: 5 layers (preparation range: 2-30 layers)

[0069] Elastic modulus: 135.7±3.9.

[0070] Figure 6 .Flowchart of the application of PGS composite multi-level microporous scaffold as negative pressure interface material. The sterilized material is cut according to the shape and size of the wound surface, and then covered on the wound surface; the wound surface and material are sealed with a sticky film, the negative pressure device is turned on, and the excess tissue exudate is removed from the drainage tube, and the basal tissue granulation grows along the negative pressure direction.

[0071] Figure 7 .SD rat wound model, the effect of PCL / PGS as negative pressure interface material on day 0 of treatment.

[0072] Figure 8 .SD rat wound model, the effect of PCL / PGS as negative pressure interface material after 7 days of treatment.

[0073] Fig. 9 .SD rat wound model, PCL / PGS used as negative pressure interface material for 14 days, stained sections under microscope.

[0074] Fig.10 .SD rat wound model, PGS was used as the negative pressure interface material, and the secondary pore size was 0.1 mm, which could not provide adequate drainage and no granulation tissue growth.

[0075] Fig.11 .SD rat wound model, PGS was used as the negative pressure interface material, and the secondary pore size was 0.2mm. During negative pressure treatment, the material degraded too quickly, the pores collapsed, and adequate drainage was impossible.

[0076] Fig.12 .In the SD rat wound model, silk fibroin was used as the negative pressure interface material. The material degraded too quickly, the voids collapsed, and the degraded part blocked the drainage tube, making drainage impossible.

[0077] Fig.13 .SD rat wound model, negative pressure interface material constructed with PCL foam material, effect after 7 days of negative pressure treatment; no granulation tissue can be observed on the surface of the material. DETAILED DESCRIPTION

[0078] The present invention will be further described below in conjunction with examples and accompanying drawings. These examples should be understood to be only for illustrating the present invention, but not to limit the scope of the present invention. Without departing from the spirit and scope of the present invention, changes and advantages that can be imagined by those skilled in the art are all included in the present invention, and are protected by the appended claims and equivalents.

[0079] Example 1 Preparation of negative pressure interface material

[0080] like Figure 2-3The preparation method of the negative pressure interface material shown is: PGS prepolymer and biomaterial PCL are dissolved in tetrahydrofuran in a ratio of 9:1 and 4:1 respectively to obtain a solution. The obtained solution is stirred and mixed with 5-50μm sodium chloride salt particles obtained by crushing, filtering and screening to obtain a mixture. The mass ratio range of the composite material formed by PGS prepolymer and biomaterial PCL and the salt particles in the solution is: 1:1. The mixture is ventilated or heated to volatilize a part of the solvent so that the shape is paste-like and has good extrudability and the ability to maintain the shape. The obtained mixture is used as a composite ink for 3D printing, and the required printing model and printing parameters are set. The printing parameters include: printing needle size (1mm), printing path spacing (4mm), printing temperature (100℃), extrusion pressure (1bar), and printing speed (100mm / s). The structure of the 3D printed composite material containing salt particles is placed in a high temperature and vacuum environment, and the temperature is set to 120℃ and the vacuum degree is 0.1Mpa. It is maintained for 24 hours to allow PGS to solidify and cross-link to form a stable structure. The 3D printed structure is required not to collapse, shrink, oxidize, or thermally decompose significantly during the vacuum and thermal curing process. It is further immersed in a 75% ethanol solution to dissolve and remove the internal salt particles and the residual PGS prepolymer that has not been completely reacted, and the water and solvents such as ethanol are removed by air drying, heating, and freeze drying, thereby obtaining a negative pressure interface material containing multi-level micropores.

[0081] The general view and scanning electron microscopy of negative pressure interface materials, such as Figure 4-5 shown.

[0082] Example 2 Wound bed treatment and drainage process description

[0083] Basic treatment of the wound bed: (1) Disinfect the area 5-8 cm around the wound and clean the wound base with saline. Reduce purulent and bloody secretions. (2) Inspect the traumatic wound and remove any foreign matter that may be present. (3) Perform sharp debridement and enzymatic debridement to completely remove necrotic tissue. The wound bed should be ready with no large amount of necrotic tissue, no large amount of purulent secretions, a bright red wound bed base, and abundant blood supply.

[0084] like Figure 6 As shown, the negative pressure interface material prepared in Example 1 of the present invention is cut to make its shape match the wound defect.

[0085] After the wound bed is prepared, the negative pressure interface material prepared in Example 1 of the present invention can be conformably fitted on the wound, and the wound and the surrounding normal skin are covered with a closed film and then sealed; finally, the suction cup and the drainage tube are connected to the wound at one end and the liquid storage tank at the other end, and the negative pressure source is started after setting the negative pressure and other parameters. Recommended negative pressure mode: continuous negative pressure, non-drip irrigation mode. Recommended negative pressure: 125 mmHg. The composite material should be fitted to the soft tissue around the wound, and the following anatomical structures should be excluded: 1. Various directly exposed blood vessels 2. Internal organs 3. Tumor tissue.

[0086] Example 3 Negative pressure interface material-SD rat wound model

[0087] Specific implementation method: The full-thickness skin of the back of SD rats was excised, and negative pressure therapy was performed using the negative pressure interface material of the PGS composite material prepared in Example 1 of the present invention. Figure 7 As shown, the left material is a 10% PCL / PGS composite negative pressure interface material, and the right material is a 20% PCL / PGS composite negative pressure interface material; after 7 days of negative pressure, the wound infection and granulation growth effects are as follows Figure 8 As shown; after 14 days of negative pressure, the effect is shown in tissue sections, such as Figure 8 shown.

[0088] It can be seen that the two negative pressure interface materials in different proportions prepared in Example 1 of the present invention can meet the requirements of negative pressure drainage therapy: during the negative pressure drainage, the degradation rate is slow, which can ensure the integrity of the structure and fully drain the negative pressure therapy; after 7 days of treatment, granulation tissue growth / cell proliferation can be seen in the secondary pores of the two materials in different proportions; after 14 days of treatment, under a microscope, the tissues around the scaffold fibers are tightly adhered, and the degradation of the scaffold fibers can be observed: the diameter of the printed scaffold fibers is 450 μm, and after 14 days the diameter is in the range of 100-200 μm.

[0089] Example 4 (Comparative Example)

[0090] The specific wound bed treatment process is the same as that of Examples 3 and 4 of the present invention, except that the negative pressure interface material is replaced with a negative pressure interface material constructed with pure PGS material, such as Fig.10 and Fig.11 As shown. Fig.10 In the experiment, the material was 5 layers, about 3mm thick, the secondary hole size was 0.1mm, and it was cut into 1cm circles. Negative pressure treatment was tried for 7 days. From the third day of treatment, the negative pressure therapy device prompted an alarm, and the drainage tube could not drain. After opening it, it was found that the wound secretions were not fully drained and the granulation tissue did not grow. Fig.10In the experiment, the material had 5 layers, was about 3 mm thick, and the secondary hole size was 0.2 mm. It was cut into 1 cm circles and negative pressure treatment was attempted for 7 days. After opening, it was seen that large chunks of the material had degraded and mixed with secretions and tissues, making it difficult to distinguish the boundaries, and it was unable to maintain its own structure as a scaffold for granulation proliferation.

[0091] Therefore, it is shown that the negative pressure interface material constructed by pure PGS material degrades too quickly, the pores collapse, and it is unable to fully drain (see Fig.10 ).

[0092] Example 5 (Comparative Example)

[0093] The specific wound bed treatment process is the same as that of Examples 3 and 4 of the present invention, except that the negative pressure interface material is replaced with a negative pressure interface material constructed with natural degradable silk fibroin material. The material is 2 mm thick and 1 cm round. Negative pressure treatment is attempted for 7 days. From the second day of treatment, the negative pressure therapy device prompts a blockage alarm and the drainage tube cannot drain.

[0094] Therefore, it is shown that the negative pressure interface material constructed by natural degradable silk fibroin material degrades too quickly, the gap collapses, and drainage cannot be completed (see Fig.12 ).

[0095] Example 6 (Comparative Example)

[0096] The specific wound bed treatment process is the same as that of Examples 3 and 4 of the present invention, except that the negative pressure interface material is replaced with a negative pressure interface material constructed with PCL foam material, the foaming pore size is 250-350 μm, and the negative pressure treatment effect is 0 / 7 days later; no granulation tissue can be observed on the surface of the material (see Fig.13 ). (This material is biodegradable, but not a bioelastic material. It has pores and can drain. However, it is harder than human soft tissue and can cause friction to surrounding soft tissue, leading to inflammation and infection.)

[0097] The protection content of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention and are protected by the attached claims.

Claims

1. A negative pressure interface material, characterized in that: It includes bioelastic materials and biomaterials.

2. The negative pressure interface material according to claim 1, characterized in that: The composition and content of the negative pressure interface material are: 40-100% bioelastic material and 0-60% biomaterial.

3. The negative pressure interface material according to claim 1, characterized in that: The negative pressure interface material is a multi-level structure: the primary structure is the overall macroscopic appearance of 3D printing, the secondary structure is the 3D printed grid drainage channel, and the tertiary structure is the micropores inside the printed fiber unit.

4. The negative pressure interface material according to any one of claims 1 to 3, characterized in that: The bioelastic material is PGS; the biomaterial is selected from one or more of PCL, PLGA, PLA, PGA, and PLCL.

5. A method for preparing a negative pressure interface material, characterized in that: The following steps are involved: (1) dissolving the bioelastic material and the biomaterial in an organic solvent to obtain a solution; (2) stirring and mixing the solution obtained in step (1) with salt particles to obtain a mixture; (3) using the mixture obtained in step (2) as a composite ink for 3D printing to obtain a structure; (4) The structure obtained in step (3) is cured and cross-linked, and the negative pressure interface material is obtained by dissolving salt particles and freeze-drying.

6. The method according to claim 5, characterized in that In step (1), the bioelastic material is PGS; the biomaterial is selected from one or more of PCL, PLGA, PLA, PGA, and PLCL; the organic solvent is selected from one or more of acetone, tetrahydrofuran, hexafluoroisopropanol, and dichloromethane; the mass ratio of the bioelastic material to the biomaterial is 40-100%:0-60%; the total mass of the bioelastic material and the biomaterial is dissolved in the organic solvent at a ratio of 1-50%.

7. The method according to claim 5, characterized in that In step (2), the salt particles are selected from one or more of sodium chloride, potassium chloride, and sodium sulfate; the particle size range of the salt particles is: 1-100 μm; the mass ratio of the total mass of the bioelastic material and the biomaterial in the solution to the salt particles is 1:0.5-1:

5.

8. The method according to claim 5, characterized in that In step (3), the 3D printing parameters include: printing needle size 0.1-1mm, printing path spacing 0.2-5mm, printing temperature -20 to 150°C, extrusion pressure 0.01-1bar, and printing speed 0.1-100mm / s.

9. The method according to claim 5, characterized in that In step (4), the curing and cross-linking temperature is 80-180°C, the vacuum degree is -0.01 to -0.1 MPa, and is maintained for 12-48 hours.

10. The negative pressure interface material prepared by the method according to any one of claims 5 to 9.

11. Use of the negative pressure interface material as claimed in claim 1 or 10 in the treatment of acute or chronic wounds, or in the repair of human soft tissue defects and injuries.

Citation Information

Cited By

  • Active material repair patch and preparation method thereof

    CN119925669A